2007
DOI: 10.1090/s0033-569x-07-01082-9
|View full text |Cite
|
Sign up to set email alerts
|

A blow-up criterion for a degenerate parabolic problem due to a concentrated nonlinear source

Abstract: Abstract. Let q, a, b, and T be real numbers with q ≥ 0, a > 0, 0 < b < 1, and T > 0. This article studies the following degenerate semilinear parabolic first initial-boundary value problem,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…It can be shown that, the positive solution of (3.3)-(3.4) exists and is unique [7,8]. Furthermore, for any fixed ratio r = a/b, there exists a critical value a * such that if a a * , then there is a quenching time T a , T a < ∞, and…”
Section: Decompositions For Singular Reaction-diffusion Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be shown that, the positive solution of (3.3)-(3.4) exists and is unique [7,8]. Furthermore, for any fixed ratio r = a/b, there exists a critical value a * such that if a a * , then there is a quenching time T a , T a < ∞, and…”
Section: Decompositions For Singular Reaction-diffusion Problemsmentioning
confidence: 99%
“…The phenomenon is called quenching, which is different from traditional blowup problems [1][2][3][4][5][6][7][8][9]21,38,54]. A particular value of a * depends on the structure of the model problem considered.…”
Section: Decompositions For Singular Reaction-diffusion Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…When α = 1, the operator L α becomes the classical heat operator L 1 u = u t − u x x , and the effects of the nonlinear concentrated source on the semilinear problems were studied by many mathematicians. For example, Chan, Chan and Boonklurb, Chan and Tian, and Chan and Tragoonsirisak studied the behavior of the continuous solution of the problems for different types of parabolic operators including semilinear, degenerate parabolic operators with different nonlinear forcing term in different domains.…”
Section: Introductionmentioning
confidence: 99%
“…By analyzing its corresponding nonlinear Volterra equation at the site of the concentrated source, they showed that blowup can be prevented by locating the nonlinear source sufficiently close to the boundary of the domain. Chan and Boonklurb [1] studied the following degenerate semilinear parabolic first initial-boundary value problem with a concentrated source at b ∈ (0, 1) on a bounded domain:…”
mentioning
confidence: 99%